Engineering cardiolipin binding to an artificial membrane protein reveals determinants for lipid-mediated stabilization - Abramsson, Mia L; Corey, Robin A; Skerle, Jan L; Persson, Louise J; Anden, Olivia; Oluwole, Abraham O; Howard, Rebecca J; Lindahl, Erik; Robinson, Carol V; Strisovsky, Kvido; Marklund, Erik G; Drew, David; et al. (eLife, 2025)
Integral membrane proteins carry out essential functions in the cell, and their activities are often modulated by specific protein-lipid interactions in the membrane. Here, we elucidate the intricate role of cardiolipin (CDL), a regulatory lipid, as a stabilizer of membrane proteins and their complexes. Using the in silico-designed model protein TMHC4_R (ROCKET) as a scaffold, we employ a combination of molecular dynamics simulations and native mass spectrometry to explore the protein features that facilitate preferential lipid interactions and mediate stabilization. We find that the spatial arrangement of positively charged residues as well as local conformational flexibility are factors that distinguish stabilizing from non-stabilizing CDL interactions. However, we also find that even in this controlled, artificial system, a clear-cut distinction between binding and stabilization is difficult to attain, revealing that overlapping lipid contacts can partially compensate for the effects of binding site mutations. Extending our insights to naturally occurring proteins, we identify a stabilizing CDL site within the E. coli rhomboid intramembrane protease GlpG and uncover its regulatory influence on enzyme substrate preference. In this work, we establish a framework for engineering functional lipid interactions, paving the way for the design of proteins with membrane-specific properties or functions.
Keywords: DNA vazebné proteiny; vazba proteinů; simulace molekulární dynamiky; E. coli; Protein Binding; endopeptidasy; lipid binding; membrane protein; kardiolipiny; proteiny z Escherichia coli; Escherichia coli; DNA-Binding Proteins; Protein Engineering; structural biology; Cardiolipins; Escherichia coli Proteins; membránové proteiny; Endopeptidases; Membrane Proteins; mass spectrometry; Molecular Dynamics Simulation; proteinové inženýrství; molecular biophysics